Agonist-activated cobalt uptake identifies divalent cation—Permeable kainate receptors on neurons and glial cells - Pruss, Rebecca M.; Akeson, Rachel L.; Racke, Margaret M.; Wilburn, Jennifer L. (Neuron (Cambridge, Mass.), 1991)
Activation of kainate receptors causes Co 2+ influx into neurons, type-2 astrocytes, and O-2A progenitor cells. Agonist-activated Co 2+ uptake can be performed using cultured cells or fresh tissue slices. Based on the pattern of response to kainate, glutamate, and quisqualate, three functionally different kainate-activated ion channels (K1, K2, and K3) can be discriminated. Co 2+ uptake through the K1 receptor was only activated by kainate. Both kainate and glutamate activated Co 2+ uptake through the K2 receptor. Co 2+ uptake through the K3 receptor was activated by all three ligands: kainate, glutamate, and quisqualate. Co 2+ uptake occurred through a nonselective cation entry pathway permeable to Co 2+, Ca 2+, and Mn 2+. The agonist-dependent activation of divalent cation influx through different kainate receptors could be correlated with expression of certain kainate receptor subunit combinations. These results are indicative of kainate receptors that may contribute to excitatory amino acid-mediated neurotoxicity.